My Two Border Towns - Bowles, David (David O.); Meza, Erika (New York : Kokila, 2021)
"A boy and his father cross the United States-Mexico border every other Saturday, visiting their favorite places, spending time with family and friends, and sharing in the responsibility of community care"--
Keywords: Fathers and sons -- Juvenile fiction; City and town life -- Juvenile fiction; Mexican Americans -- Juvenile fiction; Emigration and immigration -- Juvenile fiction; Fathers and sons -- Fiction; City and town life -- Fiction; Mexican Americans -- Fiction; Emigration and immigration -- Fiction; United States -- Juvenile fiction; Mexico -- Juvenile fiction; United States -- Fiction; Mexico -- Fiction; Picture books